Informal Street Vendors in Rio de Janeiro Case study of three formalization process - Madeira da Silva, Teresa; Monte, Marianna (International RC21 Conference 2013 Session 09.2: Urban (in)formality: tensions, conflicts and breakups in the struggle to belong, 2013)
This article will approach the informal street vending activities in the public spaces of Rio de Janeiro. Informality in general represents a challenge for the society and the governments due to its polymorphic nature and ubiquity. The informal street vending involves economic, social and urban characteristics that need to be addressed by the state. The central issue of this work is the study of the interactions in the public space between informal street vendors and the governmental institutions, and its consequences, as e. g. the formalization process. The research was based on three cases of street vendors formalization processes in Rio de Janeiro: Camelódro da Uruguaiana, Centro Municipal Luiz Gonzaga de Tradição Nordestinas and Mercado Popular da Rocinha. It is concluded that the legalization of informal street vending is responsible for the integration of certain low-income groups. However, these measures are relevant only in the short term, because the main cause of informal street vending is the endemic lack of formal jobs. Other conclusion is that the legalization must be intensively monitored and conceived as a process that must be constantly rethought and corrected. Only in this way beneficial results can be ensured to all stakeholders.